PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS III MI NURUL HUDA 3 KOTA BOGOR - Ananda Rizkiya Azzahwa; Muhyani; Amran (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to determine the effect of the Game Based Learning model on students' learning interest in Natural Sciences (IPA) subjects in the third grade at MI Nurul Huda 3 Kota Bogor. The research method used was quantitative with a quasi-experimental approach and a Nonequivalent Control Group Design. The research sample consisted of two classes: the experimental class which used the Game Based Learning model, and the control class which used conventional learning. The instrument used was a learning interest questionnaire that had been tested for validity and reliability. The results showed a significant increase in learning interest among students in the experimental class after the implementation of the Game Based Learning model. Based on the t-test statistical analysis, a significance value of < 0.05 was obtained, indicating a significant effect of the Game Based Learning model on students' learning interest. Therefore, this model is recommended as an effective alternative to enhance student engagement, especially in science learning.